2003
DOI: 10.1080/0268093032000042227
|View full text |Cite
|
Sign up to set email alerts
|

The political economy of skill and the limits of educational policy

Abstract: In the UK policy context, skills, education and learning are seen as a universal solution to a vast array of economic and social problems. In challenging this view, this paper argues that those educationalists calling for progressive reforms to the education system need to acknowledge the reality of the contemporary workplace and the institutional context of UK capitalism. When it comes to the question of how the UK might move towards a more inclusive high skills society, no matter where we start to look -be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 71 publications
2
20
0
Order By: Relevance
“…Ranson (2003) argues that the preoccupation with specifying targets and measuring outcomes presents a quantifiable model of quality which distorts the practice of public services. It has been identified that as a result of this context the main endeavour of front-line workers is to meet the output measures (Colley and Hodkinson, 2001;Lloyd and Payne, 2003). In this sense, accountability for externally defined objectives affects the way services are delivered (Barrett, 2004;Ranson, 2003).…”
Section: Realistic Expectations: Accounting For Young People's Progrementioning
confidence: 99%
See 1 more Smart Citation
“…Ranson (2003) argues that the preoccupation with specifying targets and measuring outcomes presents a quantifiable model of quality which distorts the practice of public services. It has been identified that as a result of this context the main endeavour of front-line workers is to meet the output measures (Colley and Hodkinson, 2001;Lloyd and Payne, 2003). In this sense, accountability for externally defined objectives affects the way services are delivered (Barrett, 2004;Ranson, 2003).…”
Section: Realistic Expectations: Accounting For Young People's Progrementioning
confidence: 99%
“…The difference was largely determined by the wider social and economic context and, in particular, the lack of employment opportunities for young people (Roberts, 1995;Allard, 1996). In an increasingly skilled and qualification driven workforce (DfES, 2002;Lloyd and Payne, 2003), even when a young person progressed to a stage where employment was an option, for those without formal qualifications, or sufficient literacy and numeracy skills, it was difficult to find opportunities in the labour market.…”
Section: Measuring 'Success'mentioning
confidence: 99%
“…Some educationists, according to Lloyd and Payne (2003), have responded enthusiastically to these knowledge-economy discourses. Their 'seduction' is the promise of a workforce that will be better educated and less hierarchical, as the deep-rooted divides between academic/vocational education and mental/muscle labour will supposedly dissolve in a post-Fordist knowledge-based workplace.…”
Section: What Counts As Knowledge? Bifurcations and Exclusionsmentioning
confidence: 99%
“…If this possibility becomes realised, then power relations governing workplaces would shift to reward those with intellectual skills rather than simply 'those at the top'. Other educationists have argued that, if decoupled from the economy, the vision of highly-skilled, learning-oriented and creative citizens can lead to an actively democratic and socially just society (Avis 2000, in Lloyd andPayne 2003).…”
Section: What Counts As Knowledge? Bifurcations and Exclusionsmentioning
confidence: 99%
“…It is arguable though, that connecting a forecasted labour demand with supply requires a great number of institutional arrangements and socio-economical reforms that must accompany a labour supply reform (ibid; Corrales, 1997;Whitley, 2001;Lloyd & Payne, 2003). It is also true that even in today's manpower forecasting efforts the study of the supply side of the labour market remains relatively underexplored (Willems, 1996:1).…”
Section: Structural Unemployment and Labour Market Imbalancesmentioning
confidence: 99%